Acclimater les outils de projet pour la transformation des territoires littoraux - Atelier Georges; meat architectures; Mathieu Delorme; Félicien Pecquet-Caumeil; Thibault Barbier; Lucille Bricks; Chloé Picard (Projets de Paysage)
Coastal areas are the first to be affected by changes in the way projects linked to climate change are addressed. The lack of certainty in scientific projections of coastal changes, the constant interaction between spatial and temporal dimensions, and the diversity of uses and interests involved make it difficult to draw up land-use and development plans fit for purpose. Under such conditions, is development planning, in the sense of a forward-looking narrative bringing together different stakeholders around a shared vision for the transformation of a territory, still a viable method? And if so, does this not change the way the landscape architect approaches development planning? This article sets out to explore possible answers by drawing on three original experiences which explore new narratives in projects reshaping coastal fringes threatened by climate change.